EVALUATION OF ANTIBACTERIAL POTENTIAL OF LEAF AND LEAF DERIVED CALLUS EXTRACTS OF ORTHOSIPHON ARISTATUS (BLUME) MIQ. - Reshi, Nissar Ahmad; Shankarsingh, Sudarshana Mysore; Hodiyala, Girish Vasanaika (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To evaluate the antibacterial efficacy of chloroform, petroleum ether, ethyl acetate, methanol, ethanol and aqueous extracts of leaf and leaf derived callus of Orthosiphon aristatus against Bacillus cereus, Bacillus subtiltis, Staphylococcus aureus, Streptococcus pyogenes, Enterobater aerogenes, Escherichia coli, Proteus mirabilis, and Klebseilla pneumoniae. Methods: The leaf segments were cut into small pieces of size 1-2 sq. cm and were cultured on Murashige and Skoog solid medium supplemented with different auxins alone and in combination. Antibacterial efficacy was performed by disc diffusion method followed my MIC determination by two fold serial dilution method. Leaf and leaf callus extracts were subjected to the qualitative phytochemical analysis. Results: Maximum callus formation percentage was obtained from the leaf segments cultured on MS medium supplemented with 2, 4-D (2 mg/l). Ethanolic leaf extract showed maximum inhibition activity with 28 mm zone of inhibition against P. mirabilis with MIC value of 0.32 mg/ml. Out of the callus extracts, ethanolic callus extract showed the maximum bio-efficacy against S. aureus with 26 mm zone of inhibition and MIC value of 0.64 mg/ml. Results revealed that both leaf and leaf derived callus are effective against Gram positive and Gram negative test bacteria. Conclusion: The bioefficacy study confirms the strong antibacterial potential of leaf and leaf derived callus of O. aristatus. Â 